Do Consumers Want to Create Shared Values? Building Trust in Times of Whitewashing - Joanna Lemańczyk; Magdalena Stefańska (Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie)
Objective: This article looks at consumer behaviour in the fast-moving consumer goods (FMCG) market in response to actions undertaken by organisations to create shared value. The main objectives of the paper are twofold: to explore the concept of creating shared value (CSV), and explain the forces at work on the demand side that encourage willingness to participate in support activities. The study also identifies stimuli and inhibitors that act as motivators and constraints in the creation of shared value.